The Mediating Role of Product Performance on the Effect of Process Integration with Suppliers on Firm Performance - Bülent Yıldız; Ahmet Çetindaş (Journal of Transportation and Logistics)
This study investigates the mediating role of product performance on the effect of the supplier process integration on Firm performance. Additionally, the moderator effect of market uncertainty on the effect of process integration on firm performance is also analyzed. For this purpose, data were collected by surveys from 156 manufacturing companies operating in Istanbul. A structural equation model was established and analyzed. As a result of the analysis, it was found that process integration had a positive effect on company performance. In addition, it has been determined that product performance has a positive effect on firm performance. The mediation role of product performance on the effect of process integration on firm performance was made by a bootstrap method. The mediating role of product performance could be found but the moderating role of market uncertainty could not be proven.